The Prevalence of Anatomical Variations of the Median Nerve in the Carpal Tunnel: A Systematic Review and Meta-Analysis. - Brandon Michael Henry; Helena Zwinczewska; Joyeeta Roy; Jens Vikse; Piravin Kumar Ramakrishnan; Jerzy A Walocha; Krzysztof A Tomaszewski (PLoS ONE)
Background and objective The course and branches of the median nerve (MN) in the wrist vary widely among the population. Due to significant differences in the reported prevalence of such variations, extensive knowledge on the anatomy of the MN is essential to avoid iatrogenic nerve injury. Our aim was to determine the prevalence rates of anatomical variations of the MN in the carpal tunnel and the most common course patterns and variations in its thenar motor branch (TMB). Study design A systematic search of all major databases was performed to identify articles that studied the prevalence of MN variations in the carpal tunnel and the TMB. No date or language restrictions were set. Extracted data was classified according to Lanz's classification system: variations in the course of the single TMB--extraligamentous, subligamentous, and transligamentous (type 1); accessory branches of the MN at the distal carpal tunnel (type 2); high division of the MN (type 3); and the MN and its accessory branches proximal to the carpal tunnel (type 4). Pooled prevalence rates were calculated using MetaXL 2.0. Results Thirty-one studies (n = 3918 hands) were included in the meta-analysis. The pooled prevalence rates of the extraligamentous, subligamentous, and transligamentous courses were 75.2% (95%CI:55.4%-84.7%), 13.5% (95%CI:3.6%-25.7%), and 11.3% (95%CI:2.4%-23.0%), respectively. The prevalence of Lanz group 2, 3, and 4 were 4.6% (95%CI:1.6%-9.1%), 2.6% (95%CI:0.1%-2.8%), and 2.3% (95%CI:0.3%-5.6%), respectively. Ulnar side of branching of the TMB was found in 2.1% (95%CI:0.9%-3.6%) of hands. The prevalence of hypertrophic thenar muscles over the transverse carpal ligament was 18.2% (95%CI:6.8%-33.0%). A transligamentous course of the TMB was more commonly found in hands with hypertrophic thenar muscles (23.4%, 95%CI:5.0%-43.4%) compared to those without hypertrophic musculature (1.7%, 95%CI:0%-100%). In four studies (n = 423 hands), identical bilateral course of the TMB was found in 72.3% (95%CI:58.4%-84.4%) of patients. Conclusions Anatomical variations in the course of the TMB and the MN in the carpal tunnel are common in the population. Thus, we recommend an ulnar side approach to carpal tunnel release, with a careful layer by layer dissection, to avoid iatrogenic damage to the TMB.